THREE PRINCIPLES OF MANAGING COMPLEX SYSTEMS - Vyshnivsky, O. V (Problems of Informatization and Management, 2021)
Three principles of control of complex systems on an example of the decision of a problem of electromagnetic compatibility of set of the regular antennas placed on the vehicle are formulated.